SERUM GHRELIN LEVELS DURING FRACTURE HEALING AND IMMUNOHISTOCHEMICAL INVESTIGATION OF GHRELIN IN BONE TISSUE - Emeli, Adem; Inanmaz, Mustafa Erkan; Isik, Cengiz; Bentli, Recep; Karakurt, Locman; Belhan, Oktay (Carbone Editore, 2014)
Background: Ghrelin is a hormone with efficacy on increasing osteoblastic cell proliferation, differentiation, growth hormone release, and preventing apoptosis. The present study aimed to investigate whether ghrelin has a role in bone fracture healing process and presence in the bone tissue. Patients and methods: Blood samples of 10 patients, who underwent surgery for fracture repair, were obtained for 4 times in the manner that; before fracture stabilization (preoperative) and on the postoperative lst, 10th, and 60th days. Additionally, blood samples were obtained from 10 healthy subjects (control group). Ghrelin levels in serum samples were measured by enzyme-linked immunosorbent assay method and presence of ghrelin was imnzunohistochemically investigated in bone tissue samples. Results: Although no difference was found between the groups in terms of blood levels of ghrelin, it was observed that acylated ghrelin level was increased beginning from the postoperative 1st day as compared to the control group. Des-acylated ghrelin levels were also increased as compared to the controls, except for the postoperative 10th day. Ghrelin was not detected in bone tissues. Osseous union was observed in all patients of the fracture group. Conclusions: we thought that increased acylated and des-acylated ghrelin levels were contributed to fracture healing process by means of enhancing cell proliferation, preventing apoptosis, presenting anti-inflammatory and antimicrobial effect and increasing growth hormone release.
Keywords: Fracture healing; ghrelin; bone tissue